Immunoexpression of MMP-8 and MMP-9 in chronic subdural hematoma - Su, Gao-Jian; Zhang, Di; Wu, Jia-Nuo; Deng, Yu-Hang; Wu, Chu-Wei; Zhang, Xie-Jun; Huang, Xian-Jian (Frontiers in Neurology, 2022)
To determine the possible role of matrix metallopeptidase (MMP)-8 and MMP-9 in the development of chronic subdural hematoma (CSDH), we investigated their expression in CSDH. In our previous study, we analyzed hematoma fluid and peripheral blood of 83 patients with CSDH, including 17 postoperative patients. Based on these results, we included 50 people in the normal group and analyzed 20 markers in the peripheral blood of each person. In order to identify representative markers, it was assessed by using overall differential gene expression. The concentration of MMP-8 was significantly higher in the normal group than that in the preoperative and postoperative groups. The concentration of MMP-9 was significantly lower in the normal group than in both preoperative and postoperative groups. Immunohistochemistry confirmed the expression of MMP-8 and MMP-9 in CSDH membranes. In conclusion, our results provide evidence of the expression of MMP-8 and MMP-9 in CSDH. In addition, the expression of MMP-8 and MMP-9 suggests angiogenesis in CSDH formation.